Karl Marx and Religion: 1841-1846 - Clarkson, Kathleen L. (My University, 1973)
A recurrent theme throughout the writings of Karl Marx from 1841 through 1846 is his attack on religion. This thesis will first explicate the precise nature of his atheism. Then it will detail his critique of religion by means of a chronological analysis of his major early works. Finally, it will indicate some implications of his attack on religion for the "Christian Marxist" dialogue.
Keywords: Religion; Religion